Governing seeds in East Africa in the face of climate change: Assessing political and social outcomes - Westengen, O.T.; Haug, R.; Guthiga, Paul M.; Macharia, E. (Frontiers Media, 2019)
Climate change is already negatively affecting Sub Saharan African agriculture. One of the most effective ways to adapt on farm is to switch crop varieties. This technological change depends on the policies and institutions involved in governing the seed systems on which farmers rely for access to suitable seeds. Whilst the need for seed systems to adapt and become more resilient is indisputable, the question of how this is best achieved is debated. The dominant seed system development pathway promoted by international development actors is characterized by formalization and commercialization of the seed sector. In order to assess political and social outcomes of this development agenda, we compare maize seed system development in Ethiopia, Malawi and Tanzania, combining policy analysis with quantitative analysis of farmers' seed use. We show that while the development policies promoted by international donors have similar objectives in the three countries, national policies and the seed systems farmers use differ substantially. National policies are shaped by political and historical factors and established in an interplay between state institutions, international donors and private input suppliers. Drawing on a new livelihood dataset, we show that in all three countries the formalization agenda is most visible in maize seed systems, with 25, 61, and 58% of the maize farmers planting improved maize varieties in the study sites in Ethiopia, Malawi and Tanzania, respectively. The inroads of improved maize, and particularly hybrid maize, in farmers' seed systems reflects these seeds high profitability for private seed companies. The tenuous use of improved varieties in crops such as sorghum reflects the limitation of the private sector-based seed system development approach in other crops and illustrates the need for public research and governance. Comparison of households cultivating improved maize with households cultivating local maize reveals that the first group is significantly wealthier and more food secure than the latter. This suggests that better-off households are likely to benefit first from the commercial formalization agenda. We argue that climate-smart seed policies and seed system development strategies must be sensitive to differences between farming systems and different groups of farmers if they are to deliver socially fair outcomes.